From Talent to High Performance: e view of coaches, players and club coordinators on the relevant factors in the development of a Basketball player - Gonçalves, L.; Santos, A.; Tavares, F.; Janeira, M. (Cuadernos de Psicología del Deporte, 2017)
The main goal of this study was to identify a set of factors considered relevant by basketball experts in a young player’s route to high performance. The impossibility of choosing one as the most preponderant factor comes from the complex interaction between the different areas that influence the long development path of athletes to sport expertise. Our sample consisted of 14 coaches (7 of men’s level and 7 of youth level), 7 players and 7 club coordinators who were asked to give their view on the subject by means of an interview. One of the main conclusions was the decisive inuence of environmental factors, especially the family and coaches’ influence, both as promoters of the beginning of the activity and as the maintenance in it. Psychological factors – athlete’s work ethic and surpassing capacity – were also referred as having a great role on this issue. Technical, tactical and physical factors (in this order of importance) come as an asset to the young athlete. Finally, we conclude that the training process should be defying and constantly adjusted to the athlete’s needs, creating stimulus that allow the young player to develop strategies to read and understand of the game, as well as decision making processes. The context where the athlete is inserted, as well as the psychological aspects and knowledge of the game must be considered the most relevant factors.